2020
DOI: 10.1016/j.actao.2019.103506
|View full text |Cite
|
Sign up to set email alerts
|

The genetic consequences of habitat specificity for fig trees in southern African fragmented forests

Abstract: This is a repository copy of The genetic consequences of habitat specificity for fig trees in southern African fragmented forests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 83 publications
(94 reference statements)
2
14
0
Order By: Relevance
“…In contrast, genetic structure is higher between populations of two forest specialists (Ficus craterostoma and Ficus bizanae), suggesting an effect of long-term fragmentation (Deng et al, 2020). An isolation by distance pattern showed that although the fig wasps of F. craterostoma are able to transport pollen between nearby forests, distant populations are nonetheless more genetically distinct (Deng et al, 2020). The genetic structuring of F. bizanae populations is particularly high, and this possibly reflects its atypical and dioecious-like fruiting phenotype (Deng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, genetic structure is higher between populations of two forest specialists (Ficus craterostoma and Ficus bizanae), suggesting an effect of long-term fragmentation (Deng et al, 2020). An isolation by distance pattern showed that although the fig wasps of F. craterostoma are able to transport pollen between nearby forests, distant populations are nonetheless more genetically distinct (Deng et al, 2020). The genetic structuring of F. bizanae populations is particularly high, and this possibly reflects its atypical and dioecious-like fruiting phenotype (Deng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…An isolation by distance pattern showed that although the fig wasps of F. craterostoma are able to transport pollen between nearby forests, distant populations are nonetheless more genetically distinct (Deng et al, 2020). The genetic structuring of F. bizanae populations is particularly high, and this possibly reflects its atypical and dioecious-like fruiting phenotype (Deng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations